1997
DOI: 10.1046/j.1365-2958.1997.3121675.x
|View full text |Cite
|
Sign up to set email alerts
|

Autoregulation of the Escherichia coli replication initiator protein, DnaA, is indirect

Abstract: SummaryThe expression of dnaA is autoregulated, in that transcription of the gene increases when DnaA is inactivated (and initiation of replication prevented) and decreases when DnaA is supplied in excess. However, the inactivation of DnaA does not necessarily lead to increased DnaA production, as dnaA(Ts; temperature sensitive) strains which are integratively suppressed by derivatives of the plasmid R1 do not show temperatureinduced derepression. Several possible explanations for this unanticipated behaviour … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

1997
1997
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 46 publications
1
17
0
Order By: Relevance
“…DnaA is believed to function as a transcriptional regulator of many genes, including itself in E. coli (Messer et al, 1988 ;Messer & Weigel, 1997). The binding of E. coli DnaA to DnaA boxes located in the promoter regions of dnaA and polA has been shown to result in transcriptional repression (Atlung et al, 1984(Atlung et al, , 1985Braun et al, 1985 ;Braun & Wright, 1986 ;Polaczek & Wright, 1990 ;Skovgaard et al, 1998 ;Smith et al, 1997). Scanning the putative promoter regions of several genes, including, for example, dnaA, ftsY and ftsQ of M. smegmatis (Institute of Genome Research ; http :\\www.tigr.org\) and M. tuberculosis (Cole et al, 1998), revealed the presence of several nine nucleotide long sequences with one to two mismatches to the conserved DnaA box sequence TTCA\GGCACA (Madiraju et al, 1999 ;Qin et al, 1999 ;Rajagopalan et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…DnaA is believed to function as a transcriptional regulator of many genes, including itself in E. coli (Messer et al, 1988 ;Messer & Weigel, 1997). The binding of E. coli DnaA to DnaA boxes located in the promoter regions of dnaA and polA has been shown to result in transcriptional repression (Atlung et al, 1984(Atlung et al, , 1985Braun et al, 1985 ;Braun & Wright, 1986 ;Polaczek & Wright, 1990 ;Skovgaard et al, 1998 ;Smith et al, 1997). Scanning the putative promoter regions of several genes, including, for example, dnaA, ftsY and ftsQ of M. smegmatis (Institute of Genome Research ; http :\\www.tigr.org\) and M. tuberculosis (Cole et al, 1998), revealed the presence of several nine nucleotide long sequences with one to two mismatches to the conserved DnaA box sequence TTCA\GGCACA (Madiraju et al, 1999 ;Qin et al, 1999 ;Rajagopalan et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…In vitro as well as in vivo studies revealed that the expression of the dnaA gene is regulated by the interaction of its own protein product with the DnaA boxes (Atlung et al 1985;Braun et al 1985;KuÈ cherer et al 1986). However, a more indirect mode of regulation of the dnaA gene has also been suggested (Herrick et al 1996;Smith et al 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Integratively suppressed dnaA ts strains are not derepressed upon heat inactivation of DnaA (Masters et al, 1989). Integratively suppressed dnaA(Null) strains, however, are derepressed (Smith et al, 1997 ). In addition, regulation of dnaA transcription by the DnaA level does not appear to require the integrity of the dnaA-promoter DnaA box because mutation of the box to a sequence that does not bind DnaA does not result in dnaA derepression (Polaczek and Wright, 1990;Smith et al, 1997 ).…”
Section: Dnaa Protein Is a Repressormentioning
confidence: 99%
“…Integratively suppressed dnaA(Null) strains, however, are derepressed (Smith et al, 1997 ). In addition, regulation of dnaA transcription by the DnaA level does not appear to require the integrity of the dnaA-promoter DnaA box because mutation of the box to a sequence that does not bind DnaA does not result in dnaA derepression (Polaczek and Wright, 1990;Smith et al, 1997 ). Possibly other DnaA boxes with a mismatch that are present in the dnaA promoter region may substitute for the box between P1 and P2.…”
Section: Dnaa Protein Is a Repressormentioning
confidence: 99%